Health Information Seeking Behaviour of Nigerian Undergraduates on Social Media - Anaeto, Margaret Solo -; Nwokike, Obinna; Ojo, Adebowale (NIU Journal of Social Sciences; Vol 7 No 2 (2021): KIU Journal of Social Sciences, Vol. 7 No. 2, June 2021, 2021)
This study investigated the utilization of social media as sources of health information among undergraduates. It examined ways undergraduates use social media in seeking health information, the kinds of health information they seek and the frequency of seeking health information on social media. Survey research design was adopted in which questionnaire was distributed to a sample size of 200 undergraduates of Lead City University, Ibadan. The study found that undergraduates use social media as sources of health information. However, students do not seek health information from social media on a regular basis but do so only when the need arises. It was found that students are not active in health information seeking, rather they come in contact with health information on social media only when such information are sent to them or when they appear on their social media pages or when their online friends tag them to the information. Preventive healthcare information was found to be the common kind of health information undergraduates are mostly interested in. The study concluded that social media are veritable tools for undergraduates to get health information that can enhance their well being. It recommended that undergraduates should be active and intentional about seeking health information on social media. They should use them as tools for connecting with health specialists, developing and participating in health support groups and other activities that can enhance their health and wellbeing. Keywords: Health information seeking, Preventive health information Social media, Undergraduates